PLMA vs. I-gel: A comparative evaluation of respiratory mechanics in laparoscopic cholecystectomy - Bimla Sharma; Raminder Sehgal; Chand Sahai; Jayashree Sood (Wolters Kluwer Medknow Publications, 2010)
Background : Supraglottic airway devices (SADs), such as ProSealTM laryngeal mask airway (PLMA), which produce high oropharyngeal seal pressure (OSP) and have the facility for gastric decompression have been used in laparoscopic procedures. i-gel is a new SAD which shares these features with the PLMA. This study was designed to compare the respiratory mechanics of these two devices during positive pressure ventilation in anaesthetised adult patients undergoing laparoscopic cholecystectomy. Patients & Methods: The study included 60 ASA I-II adult patients scheduled for laparoscopic cholecystectomy. The patients were randomized to two groups of 30 each, with either PLMA or i-gel as their airway device. Anaesthesia and premedication were standardized for both the groups. In addition to routine monitoring, neuromuscular monitoring with TOF ratio, OSP and respiratory mechanics monitoring (dynamic compliance, resistance, work of breathing, measured minute ventilation and peak airway pressures) were employed. Fibreoptic evaluation of positioning of the devices and adverse events related to them were also compared. Results:The OSP (cm H2O) were higher for PLMA (38.9 vs. 35.6, P=0.007). The respiratory mechanics parameters using the two devices were comparable apart from the dynamic compliance, which was significantly higher with i-gel (P < 0.05). Malrotation was higher with i-gel than with PLMA (15 vs. 5, P = 0.006). Conclusion:The PLMA formed a better seal while the dynamic compliance was higher with the i-gel. Both devices provided optimal ventilation and oxygenation and the adverse events were also comparable.